RUPTURED BAKER CYST IN GOUT DISEASE: CASE REPORT - Hakan Tuna,; Mustafa Yıldız,; Ercüment Ünlü,; Ülkü Sarpkaya,; Siranuş Kokino, (Archives of Rheumatology, 2004)
A 54 year old male patient who had a diagnosis of Gout disease for 2 years was admitted to our clinic with the complaint of pain and swelling in his posterior right knee and cruris. An initial diagnosis of ruptured Baker's cyst was made, on the other hand the differential diagnosis as deep vein thrombosis was thought, further laboratory investigation including ultrasonography and magnetic resonance imaging revealed a ruptured Baker's cyst. Popliteal cysts which rupture to mimic a deep vein thrombosis can be seen in such as inflammatory arthritis. The report of a case is ruptured baker's cyst in gout. Pertinent literature on the subject is also reviewed.